Solid-state anaerobic digestion facilitates the removal of antibiotic resistance genes and mobile genetic elements from cattle manure. (February 2019) - Sun, Wei; Gu, Jie; Wang, Xiaojuan; Qian, Xun; Peng, Huiling
Graphical abstract: Highlights: Solid-state anaerobic digestion (SAD) removed over 7/10 ARGs from digestion product. The variations in the bacterial community were smaller in SAD than LAD. Firmicutes comprised 62.5% of the potential hosts for ARGs and MGEs. SAD decreased the environmental risk of ARGs in the manure digestion product. Abstract: Livestock manure is a hotspot for antibiotic resistance genes (ARGs). Solid-state anaerobic digestion (SAD) is a high efficiency livestock manure treatment, but the changes in ARGs and microbial communities during SAD are unknown. Therefore, thermophilic SAD (55 °C), mesophilic SAD (35 °C), and liquid anaerobic digestion (35 °C) were conducted to investigate the impacts of SAD on ARGs, mobile genetic elements, and microbial communities. Compared with liquid anaerobic digestion, SAD significantly reduced at least 7/10 ARGs and all of the mobile genetic elements considered, where the total abundance of ARG was 23.7% higher in the thermophilic SAD product than the mesophilic SAD product. Firmicutes and Proteobacteria were the main potential hosts for ARGs, and their decreased abundances were mainly responsible for the reductions in ARGs during SAD. This study demonstrated that SAD is a promising method for decreasing the ARGs risk in livestock manure.